2018
DOI: 10.1111/jace.15893
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electrochemical cycling on the strength of LiCoO2

Abstract: This work utilizes in situ transmission electron microscopy-based nanopillar compression to investigate the effect of electrochemical cycling on the mechanical properties of LiCoO 2 . The ultimate strength of LiCoO 2 in the pristine state, and after 1 and 11 cycles are 5.62 ± 0.22 GPa, 3.91 ± 1.22 GPa, and 2.27 ± 1.07 GPa, respectively. The reduced average yield strengths and the large standard deviations of cycled samples, relative to the pristine powder, are hypothesized to result from nonuniform accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…This inclined plane is referred to as a "cleavage plane" rather than a slip plane. 19 This motivates the present study: does single slip occur in layered oxides at values of shear stress on the order of tens or hundreds of MPa rather than several GPa? Such slip at low resolved shear stress is consistent with recent observations and calculations for NMC811 single-crystal cathodes under cyclic electrical loading: 20 slip bands were observed in NMC811 single crystals under electrochemical cycling, and the predicted shear stresses within the crystals due to charge and discharge did not exceed a few hundred MPa.…”
Section: Supplementary Materials For This Article Is Available Onlinementioning
confidence: 80%
See 2 more Smart Citations
“…This inclined plane is referred to as a "cleavage plane" rather than a slip plane. 19 This motivates the present study: does single slip occur in layered oxides at values of shear stress on the order of tens or hundreds of MPa rather than several GPa? Such slip at low resolved shear stress is consistent with recent observations and calculations for NMC811 single-crystal cathodes under cyclic electrical loading: 20 slip bands were observed in NMC811 single crystals under electrochemical cycling, and the predicted shear stresses within the crystals due to charge and discharge did not exceed a few hundred MPa.…”
Section: Supplementary Materials For This Article Is Available Onlinementioning
confidence: 80%
“…Additional, secondary slip systems can be envisaged, but these slip systems will be much stronger than the primary slip system on the basal plane; activation of several of these additional slip systems gives rise to uniform plastic straining by dislocation-mediated plasticity. Measurements 19 suggest that this occurs at an axial stress of 4 GPa.…”
Section: Supplementary Materials For This Article Is Available Onlinementioning
confidence: 95%
See 1 more Smart Citation
“…The test consists of a rigid tip (usually diamond) pressing against a flat surface of the sample creating an indentation while tracking applied load and displacement. From these data and the knowledge of the precise (calibrated) shape of the tip stress−strain curve pillar LCO, 394 Li 397 particle strength particle NMC 385 wafer-curvature using multibeam optical stress sensor biaxial stress film, 140,141,386,398−400 composite 401,402 S composite, 401 Si 138,386,399,403 /Si composite, 402 Sn, 398 Ge, 140,404 geometry, the mechanical properties can be derived using wellestablished mechanics models. Measurements will correspond to the global properties of a composite material as long as the indentation depth is much greater than the characteristic size of the constituent phases.…”
Section: Mechanical Characterization Techniquesmentioning
confidence: 99%
“…This test, often performed inside an electron microscope, gives the full uniaxial material response (stress− strain curve); however, the setup is significantly more involved. Using this approach, Feng et al 394 found that the ultimate strength of LiCoO 2 pillars was uniform in the pristine state, but upon a single (de)lithiation cycle, the ultimate strength decreased significantly and varied widely. This variation indicates that the distribution of the defects responsible for the reduced strength is nonuniform.…”
Section: Mechanical Characterization Techniquesmentioning
confidence: 99%